2018
DOI: 10.4103/ejd.ejd_333_17
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, treatment, and rehabilitation of a patient with inflammatory pseudotumor

Abstract: Inflammatory pseudotumors are a group of lesions of unknown etiology that mimic clinically and radiographically neoplasms. In the maxilla, inflammatory pseudotumors are presented with bone alterations of erosion, remodeling, and sclerosis. The diagnosis is of exclusion, where multiple biopsies are required. The present study aims to report the case of a male patient who presented with increased volume in the left maxillary region, with diagnosis after total left maxillectomy being inflammatory pseudotumor. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In a recent report by Neronov et al, 25 cases of intraosseous IPT of the jaw were reported, with the mandible being the most affected. After an extensive literature search, less than 10 cases of maxillary IPT were found, 3 , 11 , 12 all of which were osteolytic. Two cases were on the right side, and seven were on the left.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report by Neronov et al, 25 cases of intraosseous IPT of the jaw were reported, with the mandible being the most affected. After an extensive literature search, less than 10 cases of maxillary IPT were found, 3 , 11 , 12 all of which were osteolytic. Two cases were on the right side, and seven were on the left.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of IPT is not known, but various mechanisms have been suggested including immune-autoimmune, trauma and surgical inflammation ( 6 ), furthermore, it may resemble low-grade fibrosarcoma with inflammatory cells ( 6 ).…”
Section: Introductionmentioning
confidence: 99%